1977
DOI: 10.1111/j.1471-4159.1977.tb10703.x
|View full text |Cite
|
Sign up to set email alerts
|

Huntington's Chorea: Post Mortem Activity of Enzymes Involved in Cerebral Glucose Metabolism

Abstract: Abstract— The loss of at least two different cell types in the basal ganglia of the choreic brain led us to examine the activity of enzymes involved in the metabolism of glucose. Cellular ATPase, HK, G6‐PDH, PFK., LDH, GDH were measured. Post mortem stability studies indicated that these enzymes were more unstable in human brain than mouse brain. The most stable enzyme was GDH. HK activity appeared to increase after freezing, suggesting release from another compartment. PFK and G6‐PDH activity decreased by 70%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 17 publications
4
10
0
Order By: Relevance
“…Furthermore, in our experiments human brain GDH did not appear to be affected either by the interval from death to postmortem examination, o r by storage at -20°C. These findings of GDH stability in autopsy human brain are in agreement with those reported by Bird et al (1977).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, in our experiments human brain GDH did not appear to be affected either by the interval from death to postmortem examination, o r by storage at -20°C. These findings of GDH stability in autopsy human brain are in agreement with those reported by Bird et al (1977).…”
Section: Resultssupporting
confidence: 92%
“…When the values were expressed as nmol/min/mg protein, the regional distribution pattern was similar with a range from 103 to 377. Our values of GDH activity in human brain fell within the range reported for rat brain (Filla et al, 1984;Leong and Clark, 1984) and were slightly higher than those reported by Johnson (1972) for cat brain, and by Bird et al (1977) for human brain.…”
Section: Resultssupporting
confidence: 86%
“…However, this enzyme is particularly susceptible to the effect of postmortem delay, agonal state. and tissue freezing (Bird et al, 1977: Iwangoff et al, 1980 and the results could not be interpreted with confidence. Subsequent measurements in biopsied neocortex revealed no consistent reductions in the activity of this enzyme in AD (Sims et al.…”
Section: Mechanisms Of Neuronal Degenerationmentioning
confidence: 95%
“…Similarly in the occiput of affected individuals, onset of visual stimulation fails to increase P i /ATP, PCr/ATP or P i /PCr ratios or lactate accumulation, as observed in control subjects [ 66 ]. The glycolytic enzyme phosphofructokinase was diminished in the post mortem HD caudate and putamen, but not in cortex [ 68 ] ( Fig. 1 ).…”
Section: Energy Deficits In Hdmentioning
confidence: 99%